Blessing applications: how does the court balance proper scrutiny with the principle of non-intervention?. Issue 3 (28th February 2022) - Alexander, Stephen; Hooper, Katie
Abstract: The supervisory court on a blessing application generally acts without cross-examination and full disclosure and, yet, must be satisfied as to the propriety of the trustee's decision before it bestows upon a trustee the armour of a blessing. How then is this to be achieved without that stringent testing of the trustee's evidence? Recent decisions of the Royal Court of Jersey indicate that the Court does not shy away from adopting an inquisitorial role itself, by interrogating the evidence and identifying any flaws in the trustee's decision. But is such an approach consistent with the principle of non-intervention on the part of the supervisory court? This article considers these thorny issues.